Challenges Facing Innovation Management in Omani Higher Education Institutions from the Point of View of Innovative Students - Almaqbali, Marhouna Hamed; Al-Harthi , Aisha Salim; Al Abri , Khalaf Marhoon; Al Dhafri , Said Suliman (Dirasat: Educational Sciences, 2024)
Objectives: The study aimed to identify the most prominent challenges facing the management of innovations in higher education institutions in Oman from students’ points of view; before, during, and after innovation. Methods: The descriptive approach was used in the style of qualitative research according to the phenomenological research design. The semi-structured interview was used to collect data, and it was applied to thirty students participating in competitions and receiving research funding. Results: Despite the division of the detected challenges, challenges that appear at one stage may influence subsequent stages. The challenges of the pre-innovation stage include prospecting for innovative ideas, team formation, and choosing the appropriate supervisor. Moreover, personal challenges (i.e., psychological, academic, skills, and abilities), policies and laws, human resources, financial resources, and funding are examples of challenges during the innovation stage. In addition to obstacles in coordination and communication with entities, incubators, knowledge and data, and challenges related to decision-makers. Furthermore, the challenges in the post-innovation phase include human resources challenges, follow-up challenges after the end of the participation period, and the willingness of entities to adopt innovation. Likewise, marketing innovation challenges, competition with other companies, and societal challenges. Conclusion: The study recommends developing scenarios for challenges mitigation facing innovative students from the point of view of the students themselves and those who are in charge. It also suggests conducting more studies by expanding the targeted population to involve more universities as well as enlarging the sample of innovative students.